Tempted by the billionaire next door - Beharrie, Therese; Mills & Boon Forever Romance (Sydney, New South Wales : Mills & Boon Forever Romance, 2018)
When Jessica Steyn learns her delicious new neighbour is actually her best friend's brother, billionaire bad boy Dylan Nel, she's torn. After all, she's just become his sister's surrogate! Acting on their attraction would complicate things, but they're soon growing closer. Overcoming Dylan's troubled family history - and Jessica's pregnancy - seems impossible, but could the answer to their heartaches be just next door?.
Keywords: Fiction - Romance - General; Contemporary romance; Fiction - Romance - Contemporary; Australian